Evaluation of safety after optic exchange of a modular intraocular lens. Issue 10 (October 2021) - Ang, Robert Edward T.; Yoo, Paul; Liu, Jingbo
Abstract : After optic exchange, subjects receiving a modular intraocular lens had adverse event rates consistent with conventional lenses and endothelial cell loss within rates reported for standard phacoemulsification. Abstract : Purpose: To characterize safety of optic exchange using a modular lens. Setting: 3 study sites, New Zealand, Philippines. Design: Prospective clinical study. Methods: Harmoni Modular intraocular lens (HMIOL) with separate base and optic components was implanted in the study eye (monovision target −1.50 diopter). Contralateral eyes received standard monofocal IOLs. Subjects could elect optic exchange 3 months after primary implantation. Adverse events (AEs) and endothelial cell loss (ECL) were assessed through 12 months of follow-up. Results: 114 subjects successfully received HMIOL and 114 received control lens in contralateral eye. At 3 months, 65 HMIOL eyes had optic exchange because of unsatisfactory visual outcome from high monovision (exchange cohort); 49 eyes received no exchange (no exchange cohort). Exchange, no exchange, and control cohorts reported ocular AEs in 10 (15%), 6 (12%), and 14 (12%) eyes, respectively. No posterior capsular rupture occurred during optic exchange procedures. Short-term (12-month) posterior capsule opacification (PCO) evaluation showed that all eyes had PCO grade 1 or less at 12 months; no Nd:YAG capsulotomy was performed in the exchange cohort. No exchange and exchange cohorts had similar ECL at 3 months vs preoperative baseline (−4.5%, n = 48 and −4.0%, n = 65). In the exchange cohort, additional 2.7% ECL occurred 3 months after optic exchange compared with preexchange baseline; ECL was significantly below the 14% threshold ( P < .001) and was 5.8% at 12 months. Conclusions: HMIOL safety outcomes were comparable with standard monofocal IOLs; HMIOL may provide an effective method for correcting postoperative refractive errors.